PERANCANGAN APLIKASI SISTEM FORM VIRTUAL TOUR BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL - Alliong Kurniawan; Suprihadi Suprihadi (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Virtual tour is a change of flat landscape images into a round format. The virtual tour displays panoramas, videos, photos, floor plans or maps and may play sound depending on where the visitor is viewing it. In a virtual tour, visitors feel as if they are walking virtually through the scenery using a computer, television or cellphone. A virtual tour is an accurate simulation of a location that can be viewed 360 degrees, a website-based virtual tour can be accessed anytime and anywhere. Virtual tours can also be made using video recording devices such as cameras, smartphones, drones, etc., and will usually be displayed on a website. Virtual tours are useful for virtually guiding website visitors to places they want to go. When it is displayed on a website, it is necessary to have a virtual tour form to make it easier for an admin to enter data, save data, delete data, and change virtual tour data that will be displayed on the website so that it is easy for the data manager. Making an attractive and good website using the laravel framework, then using the programming languages php, html, css, and javascript. For the database using the MySQL database.